Study And Analysis Of Impact-Based Piezoelectric Energy Harvester For Wideband Output - Ng, Xue Yan (2019)
The piezoelectric energy harvester (PEH) is the piezoelectric materials that are used to produce charges when the piezoelectric transducer is either bent, compressed or stretch. It has been widely developed because it is easier to be used and has higher power density compares with electrostatic and electromagnetic energy harvester. However, due to the frequency of the ambient vibration sources is changeable and also, the frequency generated from the impact will provide a sharp peak and a narrow bandwidth which making it not ideal to efficiently operates the applications devices in real life. As the piezoelectric transducer has a high Q-factor, the operating frequency bandwidth of the piezoelectric transducer is narrowed and limited. The yielded output power of the piezoelectric transducer only can be harvested within the narrowed operating frequency bandwidth. Thereupon, the motivation of this research is to widen the operating frequency bandwidth of the vibration-based impact mode PEH so that it can be applied on self-powered RF system and operated at the ambient vibration sources’ frequency which is between 10Hz to 300Hz. For the laboratory setup, the continuous vibration impact mode experiment is conducted to characterize the performance and output efficiency of the piezoelectric disc. The additional of the interfaced plate is analyzed and included as it can enhance the output efficiency of the piezoelectric disc. Moreover, the frequency response of the piezoelectric disc is characterized by altering the proof mass and vibrating beam’s width and thickness of the designed piezoelectric power generator. The highest performance of the piezoelectric disc with the interfaced plate and vibrating beam is selected to be applied on the new design piezoelectric power generator. Three different designs of power generator are devised and different connections of combining the multiple piezoelectric discs are analyzed. Furthermore, a buck converter of LTC 3588 is applied for the purpose of stepping up the current while stepping down the harvested output voltage. This is because of the current of the PEH is not high sufficient to drive the self-powered RF system. The piezoelectric discs of P-DL piezoelectric power generator that are connected in DCTC SSP connection can harvest 0.41mW of output power with 1 g-level of the acceleration level. The self-powered RF system with DCTC SSP connection can be operated with the ambient frequency from 30Hz to 280Hz (250Hz bandwidth) which is wider about 1.56 times compared to the CTDC connections. Moreover, the charging time of the DCTC SSP connection is 71 seconds, which is shorter compares to the charging time of CTDC connections that are more than 251 seconds. The overall result justifies that this research can be applied for the electronic device such as self-powered piezoelectric based RF system in wide ambient frequency sources and appliances. A hybrid system or an incrementation of an acceleration level will be included for the future work for the purpose of enhancing the performance of the designed power generator to drive and apply on the Internet of Things (IoT) monitoring system.